Hormonal drug therapy for sexual offenders with paraphilic disorders - Suárez Moreno, Victor (2018)
through hormonal therapy. The aim of this review is to evaluate the effects of anti-androgen therapy on sexual offenders with paraphilic disorders. We searched for systematic reviews and clinical practice guidelines on anti-androgen therapy. Two systematic reviews and a clinical practice guide were selected whose evidence corresponds to case reports and observational studies. Primary outcome, sexual relapse, has only been evaluated in two comparative studies with medroxyprogesterone. Small number of participants and high percentage of dropouts do not allow conclusions to be drawn as to efficacy. Frequent adverse effects were reported. Available evidence is scant and of low quality on the efficacy of hormonal therapy with antiandrogens steroids and GnRH analogs in patients with paraphilic disorders.